Analisis Kinerja Bank Syariah Negara OKI pada Era Digital: Studi Masa Pandemi Covid-19 - Anggi Indrawati; Fadia Haya Putri; Rofiul Wahyudi (Journal Of Institution And Sharia Finance, 2022)
This study aims to analyze the performance of Islamic banks in OKI countries in the digital era during the pandemic. This research is a quantitative research with a descriptive approach. The sample in this study was selected based on a purposive sampling technique in order to obtain nine Islamic Cooperation Organization (OKI) countries with the top rankings according to the Asian Banker in 2020. Secondary data in this study were in the form of quarterly financial reports for the 2020 observation period. The data analysis technique used descriptive statistics for provides a complete picture of the financial performance of Islamic banks during the Covid-19 pandemic. The results show that the performance of Islamic banks in the nine OKI countries was not affected during the Covid-19 pandemic. On the other hand, the Covid-19 pandemic has actually encouraged the digitization of digital banking services and transactions to maintain profits during the Covid-19 pandemic.